Merleau-Ponty's phenomenal body and the study of religion - Nikkel, David Henry (Religion, 2025)
In opposition to dualism of mind over against body and matter, Maurice Merleau-Ponty offers his experiential, lived, or ‘phenomenal’ body. Meaning, in the sense of both knowledge and value, arises from our embodied engagement and mutual constitution with our natural-social world. This article argues that two types of understandings of the nature of the body are still common in religious studies, which reinscribe Cartesian dualism by opting for one side or the other. Using Merleau-Ponty's language, these are the ‘intellectualist’ body and the ‘empiricist’ body, the first reducing meaning to mind or language that controls or inscribes bodies, the second minimizing or eliminating meaning through reductive, mechanistic, physiological causation. The constructive portion of this article engages with scholars in accord with Merleau-Ponty’s phenomenal body, who work on ways to study religion as embodied, expounding upon enactive, emplaced cognition and meanings, religious or extraordinary experiences, ritual, and the evolution of religion.